A Novel 7-Days Prolonged Dietary Deprivation Regimen Improves ALT and UA After 3–6 Months Refeeding, Indicating Therapeutic Potential - Wang, Xiaoxue; Li, Zhihui; Zhao, Yancong; Yu, Yaying; Xue, Yanyan; Niu, Chenguang; Wei, Qiannan; Zhao, Zhijun; Cai, Shangyuan; Xu, Hongxia; Zhang, Chenlu; Zhang, Chenggang; et al. (Frontiers in Nutrition, 2020)
Objectives: The aim of this study was to evaluate a total fasting regimen assisted by a novel prebiotic, Flexible Abrosia (FA), in more than 7 days of continual dietary deprivation (7D-CDD). Our analysis included basic physical examinations, bioelectrical impedance analysis, and clinical lab and ELISA analysis in normal volunteers. Methods: Seven healthy subjects with normal body weight participated in 7D-CDD with the assistance of a specially designed probiotic. Individuals were assigned to take FA (113.4 KJ/10 g) at each mealtime to avoid possible injuries to intestinal flora and smooth the hunger sensation. During 7D-CDD, the subjects were advised to avoid any food intake, especially carbohydrates, except for drinking plentiful amounts of water. The examination samples were collected before CDD as self-control, at 7 days fasting, and after 7~14 days of refeeding. Three subjects were also tested after 6-m refeeding. Results: The FA-CDD regimen significantly decreased suffering from starvation, with tolerable hunger sensations during the treatment. With the addition of daily mineral electrolytes, the subjects not only passed through the entire 7D-CDD regimen but also succeed in 12~13 days total fasting in two subjects. There was a significant reduction in blood glucose, insulin, and high-density lipoprotein levels during fasting, and the blood concentrations of uric acid (UA), alanine aminotransferase (ALT), and creatine kinase (CK) were increased. However, after more than 2 months of refeeding, the disease markers ALT, GOT, and CK either remained stable or were slightly downregulated compared to their initial D0 control level. Conclusion: Our experiment has supplied the first positive evidence that, with the assistance of a daily nutritional supply of around 100 kcal total calories to their intestinal flora, human subjects were able to tolerate hunger sensations. We have found that, although 7D-CDD induced increases in UA, CK, and transferases during fasting, refeeding led the markers to become either down-regulated or unchanged compared to their initial levels. This phenomenon was further confirmed in longer-term (6 m) recovery. Our results failed to support the hypothesis that fasting induced liver damage, since ALT, GOT, and CK remained low after longer-term refeeding. Our findings indicate that the 7D-CDD regimen might be practical and that it might be valuable to design larger clinical fasting trials for improvement of health strategy-targeting in metabolic disorders.